The Development of Problem Solving-Based Learning Modules on Economic Activity Materials for Class VII Students of Marsudi Siwi Catholic Junior High School - Teodorus Dangga Wewu; Melisa Wahyu Fandyansari; Heru Sofian (Program Studi Pendidikan Ekonomi, Universitas Insan Budi Utomo, 2021)
Modules are forms of teaching materials that are made in detail with standard language and understood by students, according to age and student learning abilities, so that the level of independent learning can be increased and followed by teacher guidance Responding to the lack of teaching materials, currently it is necessary to use learning models to improve students' learning abilities and can add insight or knowledge that is not boring for students. The right teaching materials in overcoming students' boredom include learning resources in the form of teaching materials. Problem Solving is a teaching and learning activity that scientifically students can think critically, and find solutions in solving a problem. The main purpose of this learning research is to investigate and solve a problem as well as master the learning objectives and be independent in teaching and learning activities in solving problems in learning activities. The type of research used in this research is development research with a Problem Solving approach. This research was conducted for two months starting from February 22, 2021 to April 22, 2021. Based on the results of the research, the results of the presentation of the module developed got a score of 93.47% from material experts and 83.92% from media experts. Based on the results of presentations from media experts and material experts, the developed module is feasible to use.